Ethanolic leaf extract of Ocimum gratissimum ameliorates methotrexate-induced nephrotoxicity in albino rats - Adikwu, Elias; Bokolo, Bonsome (Asian Journal of Medical Sciences, 2018)
Background: Nephrotoxicity is a common adverse effect of methotrexate (MTX). Ocimum gratisimum (OG) has lots of phytochemical constituents with medicinal uses. Aims and Objectives: This study assessed the benefit of ethanolic leaf extract of OG (EEOG) against a rat model of MTX-induced nephrotoxicity. Materials and Methods: Fifty four adult albino rats randomized into 9 groups A-I of six rats per group were used for this study. Groups A and B were treated with water and corn oil as placebo and solvent control respectively. Groups C-E were treated with 50, 100 and 200 mg/kg of EEOG daily for 5 days. Group F was treated with 20mg/kg of EEOG MTX intraperiotoneally on the 5th day while groups G-I were orally pretreated with 50, 100 and 200 mg/kg of EEOG daily for 5days and 20 mg/kg EEOG of MTX on the 5th day 5. Rats were weighed, sacrificed and serum was extracted and evaluated for renal function parameters. Kidneys were excised and evaluated for oxidative stress indices and histology. Results: Treatment with MTX did not produce significant (p>0.05) effects on body and kidney weights, however, creatinine, urea, uric acid, sodium, potassium chloride and bicarbonate and malondialdehyde levels were significantly (p<0.05) increased in MTX-treated rats when compared to control. Furthermore, superoxide dismutase, catalase, glutathione, glutathione peroxidase, total protein, and albumin levels were significantly (p<0.05) decreased in MTX-treated rats when compared to control. However, MTX-induced nephrotoxic effects were significantly (p<0.05) abrogated in EEOG pretreated rats in a dose-dependent manner. Conclusion: Ethanolic leaf extract of Ocimum gratissimum contains phytochemicals that could serve as remedy for methotrexate associated nephrotoxicity. Asian Journal of Medical Sciences Vol.9(5) 2018 37-43